Physalis minima Leaves Extract Induces Re-Endothelialization in Deoxycorticosterone Acetate-Salt-Induced Endothelial Dysfunction in Rats - Dian Nugrahenny; Nur Permatasari; Mohammad Saifur Rohman (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Brawijaya, 2017)
The administration of deoxy-corticosterone acetate (DOCA)-salt can induce oxidative stress leading to decrease the bioavailability of nitric oxide (NO), increase senescence of circulating endothelial progenitor cells (EPCs), thus contributing to endothelial dysfunction. This study was aimed to investigate the effects of Physalis minima L. leaves extract on serum NO levels, circulating EPCs number, and histopathology of tail artery endothelial cells in DOCA-salt-induced endothelial dysfunction in rats. Twenty-five male Wistar rats were randomly divided into five groups: rats without any treatment (normal), rats treated with DOCA (10 mg/kgBW s.c. twice weekly) and given 0.9% NaCl to drink ad libitum for 6 weeks, and DOCA-salt-induced rats orally supplemented with P. minima leaves extract at doses of 500, 1500, or 2500 mg/kgBW for 4 weeks. Serum NO levels were measured by colorimetry. The number of circulating EPCs (CD34+/CD133+ cells) was determined by flow cytometry. The tail artery sections were histologically processed with hematoxylin-eosin staining. DOCA-salt-induced rats showed significantly (p<0.05) decrease in serum NO levels and circulating EPCs number compared to the normal. There was also more detached tail artery endothelial cells in DOCA-salt-induced rats. P. minima leaves extract at a dose of 500 mg/kgBW significantly (p<0.05) increased serum NO level and circulating EPCs number, and also induced an optimal re-endothelialization in DOCA-salt-induced rats. P. minima leave extract dose-dependently increases NO bioavailability contributing to enhanced EPCs mobilization, thereby promoting re-endothelialization in DOCA-salt-induced endothelial dysfunction in rats.